Interventional Treatment for Structural Heart Disease - Murashita, Takashi (IntechOpen, 2021)
Interventional Treatment for Structural Heart Disease is an excellent resource for healthcare professionals treating patients suffering from severe coronary artery disease and valvular disease. It includes six chapters over two sections covering such topics as percutaneous coronary intervention and transcatheter valve replacement for aortic, mitral, and tricuspid valves.